2017
DOI: 10.17509/ijal.v7i2.8132
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Views on Importance of English Proficiency and Communication Skill for Employability in Malaysia

Abstract: Employability of graduates is a concern in many countries, including Malaysia, and the high unemployment rate among graduates is often attributed to their lack of English proficiency and communication skills. These two distinctive elements are often collated, and it is important to find out which is more important to employers. The study examined the employers' views on the importance of English proficiency and communication skill for graduates to be employed in the Malaysian private sector. The data were from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 17 publications
2
82
0
7
Order By: Relevance
“…Mentors also pointed out that Thai TVE students possessed the lowest communication skills; similarly, communication skills for Malaysian students were rated quite low compared to other skills. This finding is consistent with Ting, Marzuki, Chuah, Misieng, and Jerome (2017), Abdullah and Majid (2013) and Mutalib, Kadir, Robani, and Majid ( 2014) who observed that Malaysian TVE students did not have the necessary English proficiency and communication skills for workplace communication. They cannot use English properly and lack confidence when making oral presentations (Yasin, Shaupil, Mukhtar, Ghani, & Rashid, 2010).…”
Section: Difference In Employability Skills Between Thai and Malaysiasupporting
confidence: 90%
See 1 more Smart Citation
“…Mentors also pointed out that Thai TVE students possessed the lowest communication skills; similarly, communication skills for Malaysian students were rated quite low compared to other skills. This finding is consistent with Ting, Marzuki, Chuah, Misieng, and Jerome (2017), Abdullah and Majid (2013) and Mutalib, Kadir, Robani, and Majid ( 2014) who observed that Malaysian TVE students did not have the necessary English proficiency and communication skills for workplace communication. They cannot use English properly and lack confidence when making oral presentations (Yasin, Shaupil, Mukhtar, Ghani, & Rashid, 2010).…”
Section: Difference In Employability Skills Between Thai and Malaysiasupporting
confidence: 90%
“…In Thailand as well, many employers said that communication skills have been considered as one of the key competencies valued for employment (World Bank, 2014), but most Thai TVE students are lacking in this ability, especially English proficiency (Bateman & Coles, 2017). Ting et al ( 2017) concluded that in many countries, including Thailand and Malaysia, the high unemployment rate among new graduates is often attributed to their lack of English proficiency and communication skills.…”
Section: Difference In Employability Skills Between Thai and Malaysiamentioning
confidence: 99%
“…In a study done by Ting et al, it is important to provide an English-speaking environment for Malaysian students' (Ting, Marzuki, Chuah, Misieng, & Jerome, 2017). Many students are very shy and afraid to speak English with other friends (Cole, Hermon, & Yanti, 2015).…”
Section: Theoretical Supportmentioning
confidence: 99%
“…The reports, assignments, proposals, and many more written tasks prepared by the students show that the students are still grappling to write effectively let alone writing tests. In addition, the writing skills in English are important for students to master to confirm employability in future (Suryasa et al, 2017;Ting et al, 2017). Therefore, writing abilities need to inculcated among students as early as when they are in primary level to help them develop the skills accordingly with the passage of time before the students enter the job market.…”
Section: Introductionmentioning
confidence: 99%